2018
DOI: 10.1097/id.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stress and Strain Distribution Around Splinted and Nonsplinted 6-mm Short Implants in Posterior Mandible

Abstract: Splinting adjacent short implants may provide less bone strain and stress, especially at the presence of lateral forces. Increasing the implant diameter may be effective in strain reduction, but does not seem to reduce the bone stress, regardless of the direction of the load applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Studies using finite element analysis have suggested that splinted prostheses provide less strain and stress on the marginal bone surrounding short implants. 9,10 Similar results have also been confirmed in some clinical research, 11 where splinted posterior implants shorter than 8.5 mm had a higher survival rate than nonsplinted implants after an average follow-up time of 9.7 ± 3.7 years. Nevertheless, Tang et al 12 reported that no statistically significant difference was found in marginal bone loss between splinted and nonsplinted prostheses supported by short implants no more than 8 mm after 3 to 7 years of follow-up.…”
supporting
confidence: 76%
“…Studies using finite element analysis have suggested that splinted prostheses provide less strain and stress on the marginal bone surrounding short implants. 9,10 Similar results have also been confirmed in some clinical research, 11 where splinted posterior implants shorter than 8.5 mm had a higher survival rate than nonsplinted implants after an average follow-up time of 9.7 ± 3.7 years. Nevertheless, Tang et al 12 reported that no statistically significant difference was found in marginal bone loss between splinted and nonsplinted prostheses supported by short implants no more than 8 mm after 3 to 7 years of follow-up.…”
supporting
confidence: 76%
“…Moreover, increasing the crown height space (CHS) can elevate tension in the periimplant bone [3]. Although increasing the diameter of the implant can alleviate strain, it may not necessarily decrease bone stress under both axial and oblique loads [4]. The mechanical stress tends to concentrate in the areas of bone closest to the implant, gradually decreasing towards the outer regions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies have suggested that splinted prostheses can help decrease the harmful stress and strain on the peri-implant bone. [9][10][11] A retrospective study found a higher survival rate for splinted posterior implants shorter than 8.5 mm compared to nonsplinted implants after an average follow-up time of 9.7 ± 3.7 years. 7 A recent systematic review and meta-analysis concluded that there was no difference in the marginal bone loss and prosthetic complications of splinted and nonsplinted implant restorations but splinted restorations were associated with decreased implant failure.…”
Section: Introductionmentioning
confidence: 99%